Estudo da interação de campos eletromagnéticos na faixa de micro-ondas e luz visível na cultura de Rúcula (Eruca sativa) : desenvolvimento de dispositivo para a otimização da olericultura baseado na incidência da luz - Alvares, Adriano de Souza (Universidade Federal de São Carlos, 2017)
Faced with the increase in vegetable production in Brazil to 16 million tons and the collection of 8 billion reais in 2016, studies have begun on both planting and vegetables. Information from the market of vegetables shows that lettuce is the most consumed herbaceous in the country; However the consumption of arugula has been growing over the years and is currently a strong competitor of lettuce both in consumption and in terms of economic attractiveness.Due to this growing interest in recent years, in this study we analyze the interactions - and the effects - of electromagnetic waves in the visible light range and microwaves in the production of arugula. Through the obtained results, we developed a device that guarantees the correct color (wavelength) and light tonality to optimize the germination - and therefore the production - of the arugula.The analized samples were treated with light from light emitting diode (LED) sources at wavelengths of the visible spectrum at frequencies corresponding to red, green and blue colors and still with electromagnetic radiation in the range of micro (0.3 to 300 GHz) specifically at the 2.4 GHz frequency. These treatments were performed with the 8h LED setting, 8h of solar clarity and 8h night, while the 2.4 GHz treatment remained irradiated for 24h, receiving 12h of solar clarity and 12h night. Control samples were submitted to 12h of solar clarity and 12h night. All samples were treated for 7 days.The biometric measurements (leaf size, aerial part and root), fresh mass, dry weight and humidity percentage, chlorophyll a, b, total and carotenoid measurements and quantification of macro and micronutrients as Calcium (Ca), Iron (Fe), Magnesium (Mg), Manganese (Mn), Copper (Cu), Potassium (K), Sodium (Na) and Zinc (Zn).The results shows that red LED light obtained better results in biometric characteristics, wet mass and macro and micronutrient values than indicated by ANVISA through the IDR (Recommended Daily Intake) index.The low-cost device developed, proved to be important for identifying and aiding in the parameterization of light through the appropriate use of each color and tonality of the electromagnetic radiation used, thus promoting different responses in the culture. The intellectual protection of this device with the INPI (National Institute of Industrial Property) has already been initiated through the Innovation Agency of UFSCar.The results obtained in this work with the red LED will allows the extension of this project to more sophisticated studies involving the concept of quantum coherence, as recently pointed out in a study published in the Nature journal.
Study of the interaction of electromagnetic fields in the range of microwaves and visible light in the culture of Arugula (Eruca sativa): development of a device for the optimization of olericulture based on the incidence of light
Keywords: Ondas eletromagnéticas; Sensor de luz; Eruca sativa; Electromagnetic waves; LED; Light sensor; OUTROS